Auditing Procedures and Process in the Public Sector - Jibrin, Musa Success; Nkechi, Ofor Theresa; Ejura, Success Blessing (Financial Risk and Management Reviews, 2017)
This paper examines the impact of auditing in the public sector. It delved into the perspectives of functional auditing in the public sector in view of the continue quest for accountability placed on the accounting officer. The accounting officers must, as a matter of facts and professionalism, carry out his role and responsibility in such a way that affairs of resources placed under his control are properly accounted for and stewardship report rendered periodically to the public for performance assessment. Procedure in public sector brings out the essence of accountability in the public sector and the resultant stewardship accounting. The paper commences with the paper keywords, introduction, and the body of the presentation, observations, summary and conclusions in order for the researcher to drive home his point.